Consent of a pregnant minor in the matter of artificial termination of pregnancy - Βασιλείου (Marianna Vassiliou), Μαριάννα; Σαρδέλη (Chrysanthi Sardeli), Χρυσάνθη (Bioethica, 2015)
This paper examines the issue of consent of a pregnant minor in the matter of artificial termination of pregnancy, in connection with ruling nr. 3480/1996 of the Misdemeanors Tribunal of Athens. Case facts, the ruling of the court, as well as the legal framework regarding artificial termination of pregnancy in Greece are presented. Reference is made to the concept of consent, especially when the latter concerns minors. The right of a person - and in this case of a minor - to reproduction is discussed in connection to artificial termination of pregnancy. Finally, problems that may arise from the issue of consent of a pregnant minor are cited and specific changes to the existing legal framework are proposed.